Automatic Pre-Starting of Oil-Waste Fueled Stove Based on Microcontroller and HMI - Risfendra, Risfendra; Pulungan, Ali Basrah; Parmanoan, Durain; Prayoga, Noval (invotek, 2025)
The utilization of waste oil as an alternative cooking fuel is limited by its complex ignition process, which requires preheating to reduce viscosity and ensure stable combustion. Conventional methods, such as burning tissue paper, are unsafe, inefficient, and impractical, hindering broader adoption. This study presents the development of an automatic preheating system for waste oil stoves using an ESP32 microcontroller and HMI with TFT LCD display. The system integrates a thermocouple sensor for accurate real-time temperature monitoring and an automatic cut-off mechanism to halt fuel supply during ignition failure, and includes a buzzer for audible alarms during safety shutdowns to improving operational safety. The ignition sequence employs LPG as a preheater before automatically switching to waste oil at the optimal temperature, with programmed control of the blower, igniter, and valves. Experimental results showed thermocouple measurement accuracy with an average error of 4% and high reliability in fuel transition, except at low initial temperatures (31°C and 42°C) where insufficient heating time resulted in high viscosity and transition failure. The safety system effectively prevented hazards, while the HMI provided precise control and monitoring of actuators and combustion conditions. Overall, the proposed system enhances the safety, reliability, and practicality of waste oil stoves and demonstrates potential for industry innovation and renewable energy applications. Nevertheless, the system still requires LPG for the preheating stage and continuous electrical power, which can reduce effectiveness and make it harder to use in mobile or areas without electricity.